INTEGRATED APPROACH TO LANGUAGE TRAINING OF AIR TRAFFIC CONTROLLERS - Petrashchuk, Olena (Proceedings of National Aviation University (archive), 2014)
The article deals with the issue of integrative approach to language training of air traffic controllers in air traffic control simulator. The integrative approach is viewed in terms of two elements of English communicative competency: oral speech skills (listening comprehension and speaking) and language of radiotelephony communication (radiotelephony phraseology and plain English in aviation context).